Plasma membrane nano-organization specifies phosphoinositide effects on Rho-GTPases and actin dynamics in tobacco pollen tubes. Issue 3 (18th December 2020) - Fratini, Marta; Krishnamoorthy, Praveen; Stenzel, Irene; Riechmann, Mara; Matzner, Monique; Bacia, Kirsten; Heilmann, Mareike; Heilmann, Ingo
Abstract: Pollen tube growth requires coordination of cytoskeletal dynamics and apical secretion. The regulatory phospholipid phosphatidylinositol 4, 5-bisphosphate (PtdIns(4, 5)P2 ) is enriched in the subapical plasma membrane of pollen tubes of Arabidopsis thaliana and tobacco ( Nicotiana tabacum ) and can influence both actin dynamics and secretion. How alternative PtdIns(4, 5)P2 effects are specified is unclear. In tobacco pollen tubes, spinning disc microscopy (SD) reveals dual distribution of a fluorescent PtdIns(4, 5)P2 -reporter in dynamic plasma membrane nanodomains vs. apparent diffuse membrane labeling, consistent with spatially distinct coexisting pools of PtdIns(4, 5)P2 . Several PI4P 5-kinases (PIP5Ks) can generate PtdIns(4, 5)P2 in pollen tubes. Despite localizing to one membrane region, the PIP5Ks AtPIP5K2-EYFP and NtPIP5K6-EYFP display distinctive overexpression effects on cell morphologies, respectively related to altered actin dynamics or membrane trafficking. When analyzed by SD, AtPIP5K2-EYFP associated with nanodomains, whereas NtPIP5K6-EYFP localized diffusely. Chimeric AtPIP5K2-EYFP and NtPIP5K6-EYFP variants with reciprocally swapped membrane-associating domains evoked reciprocally shifted effects on cell morphology upon overexpression. Overall, active PI4P 5-kinase variants stabilized actin when targeted to nanodomains, suggesting a role of nanodomain-associated PtdIns(4, 5)P2 in actin regulation. This notion is further supported by interaction and proximity of nanodomain-associated AtPIP5K2 with the Rho-GTPase NtRac5, and by its functional interplay with elements of Rho of plants signaling. Plasma membrane nano-organization may thus aid the specification of PtdIns(4, 5)P2 functions to coordinate cytoskeletal dynamics and secretion. Abstract : The apical plasma membrane of pollen tubes contains nanodomains where the regulatory phospholipid PtdIns(4, 5)P2 exerts a stabilizing effect on the actin cytoskeleton.